Processed Multibeam Sonar Data (version 2) from the Amundsen Sea acquired during Nathaniel B. Palmer expedition NBP0901 (2009) ... - Jacobs, Stan (Interdisciplinary Earth Data Alliance (IEDA), 2011)
This data set was acquired with a Kongsberg model EM120 multibeam sonar system during Nathaniel B. Palmer expedition NBP0901 conducted in 2009 (Chief Scientist: Dr. Stan Jacobs). These data files include Sidescan, Swath Bathymetry, Acoustic Backscatter data and were processed at sea using the open source MB-System multibeam sonar processing software. Data were acquired as part of the project(s): Collaborative Research: Sampling the ocean - sea ice interaction in the Pacific center of the Antarctic Dipole; Shedding dynamic light on iron limitation: The interplay of iron limitation and dynamic irradiance conditions in governing the phytoplankton distribution in the Ross Sea; Collaborative International Research: Amundsen Sea Influence on West Antarctic Ice Sheet Stability and Sea Level Rise, and funding was provided by the U.S. National Science Foundation. ...